Meningkatkan kompetensi pedagogik dalam pemanfaatan media dan sumber belajar melalui supervisi klinis pada guru SDN 1 Gempolrejo di semester I tahun pelajaran 2019/2020 - Wahyu Widayati (Jurnal Pendidikan Dasar, 2020)
Abstract. the purposes of this research are to increase and analyze the increasing of 1 Gempolrejo Elementary School teachers’ pedagogical competency in media and learning resources utilities through clinical supervision on the First Semester of the 2019/2020 Year Academic. The type of this research is a School Action Research (SAR). This research is held on 2 Sambongrejo Elementary School, Sub district of Tunjungan, Regency of Blora. This research is going on the middle First Semester of the 2019/2020 Year Academic. Technique of collecting data of this research is nontest technique. The instruments of collecting data of thisresearch are the sheets of observation, the sheets of questioner and camera application on the cell phone. Technique of analyzing data of this research is comparative description. The procedure of this research is Cycle Model. The conclusion of this research is 1 Gempolrejo Elementary School teachers’ pedagogical competency in media and learning resources utilitiesthrough clinical supervision on the First Semester of the 2019/2020 Year Academic increased from low category (D) become high category (B). On the Early Condition, pedagogical competency in media and learning resources utilities there was not included as high category (B). On the First Cycle, pedagogical competency in media and learning resources utilities included as moderate category (C) which 22,22% of the teachers included as high category (B). On the Second Cycle, pedagogical competency in media and learning resources utilitiesincluded as high category (B) and there was not included as moderate category (C) or even lower category.Kata kunci: Pedagogical Competence, Media and Learning Resources, Clinical Supervision